CircSPG21 ameliorates oxidative stress-induced senescence in nucleus pulposus-derived mesenchymal stem cells and mitigates intervertebral disc degeneration through the miR-217/SIRT1 axis and mitophagy - Yongbo Zhang; Sheng Yang; Xuan You; Zhengguang Li; Liuyang chen; Rui Dai; Hua Sun; Liang Zhang (Stem Cell Research & Therapy)
Abstract Background The microenvironment of intervertebral disc degeneration (IVDD) is characterized by oxidative stress, leading to the senescence of nucleus pulposus-derived mesenchymal stem cells (NPMSCs). The purpose of this study was to investigate the competitive endogenous RNA mechanism involved in the senescence of NPMSCs induced by tert-butyl hydroperoxide (TBHP). Methods Bioinformatic analysis identified differentially expressed circRNAs. Interactions among circSPG21, miR-217, and the NAD-dependent protein deacetylase sirtuin-1 (SIRT1) were validated through dual-luciferase assays, RNA fluorescence in situ hybridization and RNA immune precipitation. β-Gal staining, EdU staining, Western blotting, JC-1 assays, cell cycle analysis, and quantitative reverse transcription PCR (RT‒qPCR) were used to examine the functions of these molecules in TBHP-induced senescent NPMSCs. The therapeutic effects of circSPG21 were evaluated in a rat IVDD model. Results CircSPG21 expression was significantly decreased in both human and rat IVDD tissues, whereas miR-217 was upregulated and SIRT1 was downregulated. Overexpression of circSPG21 alleviated NPMSC senescence by reducing P21 and P53 levels and restoring mitophagy through Parkin. The protective effects of circSPG21 were mediated through the miR-217/SIRT1 axis, as SIRT1 knockdown attenuated these benefits. CircSPG21 also ameliorated disc degeneration in the IVDD rat model, highlighting its potential as a therapeutic target. Conclusion CircSPG21 reduces oxidative stress-induced NPMSC senescence through the miR-217/SIRT1 axis and mitophagy, providing new insights into IVDD and identifying circSPG21 as a potential therapeutic target for disc degeneration.